The effectiveness of government regulation (pp) no. 60 of 2008 on government internal control system in North Sumatera / Eka Nurmala Sari, Maya Sari and Abdul Mughni Fahrizan Sitompul - Nurmala Sari, Eka; Sari, Maya; Sitompul, Abdul Mughni Fahrizan (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
This study aims to see how the effectiveness of the internal control system of government in local governance North Sumatera in Indonesia. This study uses explanatory research method. The type of data are primary and secondary data and use the ordinal scale as a measurement scale. Data collection uses survey techniques with the distribution of a questionnaire to the Government of the Cities and Regencies in North Sumatra. The results showed that the internal control system of government on governance in North Sumatra is still inadequate can be proven by the physical control of assets which not inadequate, is still inadequate commitment to competence, a good working relationship with the relevant government, risk analysis, and recording and documentation, only indicator that is conducive leadership, the role of internal control apparatus, separation of duties and monitoring have adequate conditions while the rest goes into the category quite adequate.